Analyse der Vergütungsstruktur der onkologischen Kinderchirurgie im G-DRG-System - Aubert, Ophelia; Schuster, Horst; Krause, Franz; Wolff, Johannes; Knoefel, Wolfram Trudo; Boettcher, Michael; Wilms, Miriam (Monatsschrift Kinderheilkunde, 2025)
Background This study examines the distribution of case volumes in pediatric surgical treatment of solid malignancies in Germany and their corresponding reimbursement (case mix index, CMI). The impact of potentially cost-inefficient low-volume care for resource-intensive pediatric oncology cases has not yet been systematically analyzed. The findings provide an empirical foundation for optimizing the German diagnosis-related groups (G-DRG) reimbursement system for pediatric oncological surgery. Methods Hospital billing data (2020-2023) for the surgical resection of solid pediatric malignancies were categorized by organ system. Relative weightings were estimated based on the corresponding G‑DRG. Hospitals were classified according to annual case volume into high-volume hospitals (HVH, ≥10 cases), medium-volume hospitals (MVH, 5-10 cases), low-volume hospitals (LVH, 1-5 cases) and extremely low-volume hospitals (eLVH, <1 case). Results On average, 744 resection procedures were performed annually across 327 institutions. The hypothetical CMI for these procedures was 2.921. Service provision was highly decentralized: 314 (96.0%) institutions performed fewer than 5 resections per year for any given organ group. Of the institutions 15 met the criteria for MVH status in at least 1 organ group, while only 4 qualified as HVH for 1 or more organ group. Conclusion The CMI for pediatric oncological surgery is substantially higher than that for general pediatric surgery but is likely insufficient to cover the actual costs of care. The pronounced fragmentation of care, with a predominance of low-volume treatment settings, may lead to reductions in essential infrastructural resources and increase the risk of suboptimal patient treatment and outcomes.